Hypofractionated Radiotherapy in African Cancer Centers - Swanson, William; Kamwa, Francesca; Samba, Richard; Ige, Taofeeq; Lasebikan, Nwamaka; Mallum, Abba; Ngoma, Twalib; Sajo, Erno; Elzawawy, Ahmed; Incrocci, Luca; Ngwa, Wilfred (Frontiers in Oncology, 2021)
In the advent of the Coronavirus Disease (COVID-19) pandemic, professional societies including the American Society for Radiation Oncology and the National Comprehensive Cancer Network recommended adopting evidence-based hypofractionated radiotherapy (HFRT). HFRT benefits include reduction in the number of clinical visits for each patient, minimizing potential exposure, and reducing stress on the limited workforce, especially in resource-limited settings as in Low-and-Middle-Income Countries (LMICs). Recent studies for LMICs in Africa have also shown that adopting HFRT can lead to significant cost reductions and increased access to radiotherapy. We assessed the readiness of 18 clinics in African LMICs to adopting HFRT. An IRB-approved survey was conducted at 18 RT clinics across 8 African countries. The survey requested information regarding the clinic’s existing equipment and human infrastructure and current practices. Amongst the surveyed clinics, 60% reported to already practicing HFRT, but only 44% of participating clinics reported adopting HFRT as a common practice. Additionally, most participating clinical staff reported to have received formal training appropriate for their role. However, the survey data on treatment planning and other experience with contouring highlighted need for additional training for radiation oncologists. Although the surveyed clinics in African LMICs are familiar with HFRT, there is need for additional investment in infrastructure and training as well as better education of oncology leaders on the benefits of increased adoption of evidence-based HFRT during and beyond the COVID-19 era.